Preliminary genipin-crosslinked gelatin–asiaticoside injectable hydrogel for future biomaterials ink: physicochemical properties and cytocompatibility for wound repair - Razif, Raniya; Zainuddin, Andik Nisa Zahra; Zawawi, Nurul Ain; Maarof, Manira; Ahmad, Haslina; Mohd nor, Fatimah; Fauzi, Mh Busra (Taylor and Francis, 2026)
Chronic wounds remain a major healthcare concern due to delayed healing and high risk of infection. This study investigates the potential of genipin-crosslinked gelatin and asiaticoside (ASI) as innovative biomaterials ink for wound healing. Hydrogels were prepared using different concentrations of gelatin (9% w/v and 10% w/v) and asiaticoside at 0.05% w/v, with genipin employed as a natural crosslinker to improve mechanical strength. Their physicochemical characteristics, which includes swelling ratio, water vapour transmission rate (WVTR), contact angle, porosity, enzymatic degradation, and surface roughness were systematically evaluated, along with mechanical and cytotoxicity properties. Incorporation of asiaticoside enhanced hydrogel hydrophilicity, reduce porosity, and improved swelling behaviour, while preserving biodegradability and overall structural stability. The WVTR values remained within the optimal wound healing range (1500–2500 g/m2h). Furthermore, asiaticoside-loaded hydrogels demonstrated excellent cytocompatibility, supporting fibroblasts viability at lower concentrations including live/dead assay tests that were conducted. This study demonstrates that genipin-crosslinked gelatin–asiaticoside hydrogels are promising biomaterials ink for accelerated wound healing, with an initial characterization of an injectable formulation guiding their successful optimization to achieve the optimal injectability and printability for tissue engineering and three-dimenstional bioprinting (3D-bioprinting).